Perbedaan Hasil Pemeriksaan Kromium Heksavalen (Cr VI) Dengan Pengompleks 1,5 Difenilkarbazida Pada Waktu 5 Menit Dan 15 Menit Secara Spektrofotometri UV-VIS - Indah Sari; Pra Dian Mariadi; Rosnita Sebayang (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2021)
Differences of hexavalent chromium (Cr VI) examination results with complexing of 1,5 diphenylcarbazide at 5 minutes and 15 minutes by spectrophotometry uv-vis at (Balai Riset dan Standard Industri Palembang) Research and Industry Standard Center Palembang, 2017. Study Program of DIV Health Analyst, Faculty of Health Sciences of Musi Charitas Catholic University Palembang. Chromium (VI) is a carcinogenic component for humans, the amount of chromium that is safe to consume by humans is 50 - 200 μg a day. This research was an analytical comparative, conducted in The Research and Industry Standard Center Palembang. Samples were from pro-analytical chemical content made from chromium-acting susceptibility of 0,1 ppm and 0,2 ppm and the samples were given a complex of 1,5 diphenylcarbazide in the period of 5 minutes and 15 minutes. The obtained chromium examination results with complexing 1,5 diphenylcarbrazide in the period of 5 minutes were 0,0869 and 0,1775 and in the period of 15 minutes were 0,0932 and 0,1626. The data analyzed by using Wilcoxon p value and it was obtained p> 0,05. Based on this research, it was concluded that chromium examination with complexing of 1,5 diphenylcarbrazide in the period of 5 minutes and 15 minutes had no significant difference.